RANCANG BANGUN PANEL AUTOMATIC TRANSFER SWITCH (ATS) BERBASIS PHOTOVOLTAIC - Yasir Mahaseng; Maryanto Masarrang; Yusnaini Arifin; Mustofa Mustofa; Sari Dewi (Foristek, 2022)
Automatic Transfer Switch (ATS) is a device that can move the main power source to a backup power source automatically and quickly when the main power source is interrupted or the supply cuts to the load. In this study, ATS was designed based on the Arduino Nano microcontroller as an automatic control that works based on voltage readings. Using the Arduino Nano microcontroller can facilitate the process of making tools and minimize the use of components. This ATS uses the PZEM-004T voltage sensor module. The voltage sensor module functions to detect and measure the value of the PLN voltage. From the test results, it was found that the time lag between the PLN supply being cut off until the battery was supplying and ready to be loaded was an average of 2.79 seconds. Meanwhile, the time lag when the PLN supply turns on again until the battery supply is cut off and the load supply is again served by PLN is 3.07 seconds on average. Other tests found that in measuring battery resistance with a load of 20 watts, the current obtained is 1.66 amperes with a usage resistance of 27 hours, while when the load is 200 watts the current is 16.66 amperes while the resistance to use is 2.7 hours. The length of battery life is affected by the magnitude of the load.